Infectivity of Neoaplectana carpocapsae and Heterorhabditis heliothidis to pupae of the parasite Apanteles militaris - Kaya, Harry K. (Society of Nematologists, 1978)
The infectivity of Neoaplectana carpocapsae and Heterorhabditis heliothidis to Apanteles militaris, a gregarious parasite of the armyworm, was deterntined at 100. 1,000, 5,000, and 10,000 nematodes per petri dish. For both nematode species, the percentage of infected A. militaris within a cocoon cluster decreased as inoculum levels decreased. At the highest inoculum level, N. carpocapsae infected an average of 32% of the parasite pupae within a cocoon cluster, whereas H. heliothidis infected an average of 22%. Covariance analysis indicated, however, that N. carpocapsae had significantly greater infectivity than did H. heliothidis. Some of the dauer juveniles of N. carpocapsae on the body of the armyworm contacted the emerging parasites and eventually became enveloped within the silken cocoons. Dauer juveniles produced by N. carpocapsae in parasite pupae could not penetrate and escape from silken cocoons even when the cocoons were placed in a moist environment.